Humerus fracture and combined venous injury increases limb loss in axillary or subclavian artery injury. (June 2019) - Grigorian, Areg; Wilson, Samuel E; de Virgilio, Christian; Kabutey, Nii-Kabu; Fujitani, Roy M; Gabriel, Viktor; Schubl, Sebastian D; Joe, Victor; Nahmias, Jeffry
Objective: Axillosubclavian vessel injury is rare, with most cases occurring after penetrating trauma. A prior database (2002–2006) analysis demonstrated an overall limb loss rate of 2.9%, with no difference between isolated arterial axillosubclavian vessel injury and combined artery/vein axillosubclavian vessel injury. Given increases in advanced vascular surgical techniques, as well as improved multidisciplinary care and expeditious diagnosis with computed tomography angiography, we hypothesized the national rate of limb loss in patients with arterial axillosubclavian vessel injury has decreased. In addition, we attempted to identify current predictors for limb loss in arterial axillosubclavian vessel injury. Finally, we hypothesized that combined artery/vein axillosubclavian vessel injury, as well as associated brachial plexus injury will have a higher risk for limb-loss and mortality compared to isolated arterial axillosubclavian vessel injury. Methods: A retrospective analysis of the National Trauma Data Bank was performed between 2007 and 2015. All patients ≥ 18 years of age with arterial axillosubclavian vessel injury were included. The primary outcome was limb loss. After a univariable logistic regression model identified significant covariates, we performed a multivariable logistic regression for analysis. Results: Of the total 5, 494, 609 trauma admissions, 3807 patients had arterial axillosubclavian vessel injury (<0.1%). Of these, 3137 (82.4%) had isolated arterial axillosubclavian vessel injury and 670 (17.6%) had combined artery/vein axillosubclavian vessel injury. The overall limb loss rate was 2.4% (from 2.9% in 2006, p  = 0.47). After adjusting for covariates, independent risk factors for limb loss included a combined artery/vein axillosubclavian vessel injury (odds ratio = 3.54, confidence interval = 2.06–6.11, p  < 0.001), blunt mechanism (odds ratio = 7.81, confidence interval = 4.21–14.48, p  < 0.001), open repair (odds ratio = 2.37, confidence interval = 1.47–3.82, p  < 0.001), and open proximal humerus fracture (odds ratio = 8.50, confidence interval = 4.97–14.54, p  < 0.001). An associated brachial plexus injury was not associated with limb loss ( p  = 0.37). Combined artery/vein axillosubclavian vessel injury was associated with higher risk for mortality compared to isolated arterial axillosubclavian vessel injury (odds ratio = 2.17, confidence interval = 1.73–2.71, p  < 0.001). Conclusions: The national rate of limb loss in trauma patients with arterial axillosubclavian vessel injury has not changed in the past decade. A combined artery/vein axillosubclavian vessel injury is an independent risk factor for limb loss, as well as open repair. However, the strongest risk factor is an open proximal humerus fracture. An associated brachial plexus injury is not associated with increased risk of limb loss. Patients with combined artery/vein axillosubclavian vessel injury have a twofold increased risk of death compared to patients with isolated arterial axillosubclavian vessel injury.